Quercetin effects on adaptive immune response in experimental periodontitis of bacterial-immune genesis - Andrii Demkovych; Yurii Bondarenko; Vitaliy Shcherba; Vitalii Luchynskyi; Volodymyr Vitkovskyy; Volodymyr Machogan (Pensoft Publishers, 2021)
In the article was studied the effects of flavonol quercetin on indices of adaptive immune response in experimental animals on the 14th day of the experimental bacterial-immune periodontitis development. Indices of immune protection were determined by the relative number of lymphocytes with CD3+, CD4+, CD8+, CD19+, CD16+ and immunoregulatory index (CD4+ / CD8+) in intact animals and on the 14th day of inflammatory process development in periodontal tissues as well as the therapeutic effects of flavonol quercetin. As a result of the study, characterized changes associated with the activity of both the cell-mediated and humoral-immune response were found, both in the development of experimental periodontitis, and apply of flavonol. In particular, there was an increase in the animal's blood relative amount of CD8+, CD16+ cells on the 14th day, and content of CD3+, CD4+, CD19+ was decreased. In this case, the immunoregulatory index (CD4+ / CD8+) as an important index of immunological activity was decreased. The apply of flavonol quercetin in the period development of bacterial-immune periodontitis animals functional activity of the T-cell line of the immune system was increased, as evidenced percentage increase of B- and T-cells due to T-helper cells decrease as well as T-killers content during this period of inflammatory reaction in the periodontal complex, in comparison with animals, which were not treated.